THE EFFECT OF LITERACY PROGRAMMED TOWARD STUDENTS’ READING INTEREST IN ELEMENTARY SCHOOL - Della Oktafiana Akhani; Martina Napratilora; Seri Yanti Siagian (STAI Nurul Falah Airmolek, 2025)
Literacy programed give positive effect toward students’ reading interest. The research aimed to find out the effect of Literacy Programmed toward Students’ Reading Interest in Fourth and Fifth Grade at Public Elementary School of 010 Tembilahan Hulu. This research was quantitative research. The participants consisted of 25 students. It took by using random sampling technique. Data collection used questionnaires, and documentation. The data analyzed using simple linear regression. The results showed that the Fhitung 14,66 ≥ Ftabel 4,28, so Ha is received and H0 is rejected. It means that there is a significance effect between literacy program of reading fifteen minutes before learning toward Students Reading Interest at Public Elementary School of 010 Tembilahan Hulu. The results suggest that school should have fixed schedule for visiting library as a part of literacy program which help students achieve reading interest.